INTERNET SEBAGAI MEDIA MASYARAKAT VIRTUAL (Studi Kasus Penanaman Budaya Menulis Surauparabek.or.id) - Rahmi Yunita (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2018)
This study aims to find out how the use of the internet in the Surau Parabek Virtual Community in the cultivation of writing members. This qualitative field research collected data using interview techniques and documentation. The interview was done virtually by contacting the editor in chief directly. This study found that philosophically, technology is used as a tool to make it easier to interact among virtual communities. Virtual communities are people who interact no longer use space in physical form but tend to interact with virtual space in this case the internet. Surau Parabek Virtual Community conducts all cultural planting activities to write virtual community members by using the internet as a tool.